Combined effect of chitosan and water activity on growth and fumonisin production by Fusarium verticillioides and Fusarium proliferatum on maize-based media - Ferrochio, Laura Valeria (2014)
The objectives of the present study were to determine the in vitro efficacy of chitosan (0.5, 1.0, 2.0 and 3.0 mg/mL) under different water availabilities (0.995, 0.99, 0.98, 0.96 and 0.93) at 25 °C on lag phase, growth rate and fumonisin production by isolates of Fusarium verticillioides and Fusarium proliferatum. The presence of chitosan affected growth and fumonisin production, and this effect was dependent on the dose and aW treatment used. The presence of chitosan increased the lag phase, and reduced the growth rate of both Fusarium species significantly at all concentrations used, especially at 0.93 aW. Also, significant reduction of fumonisin production was observed in both Fusarium species at all conditions assayed. The present study has shown the combined effects of chitosan and aW on growth and fumonisin production by the two most important Fusarium species present on maize. Low molecular weight (Mw) chitosan with more than 70% of degree of deacetylation (DD) at 0.5 mg/mL was able to significantly reduce growth rate and fumonisin production on maize-based media, with maximum levels of reduction in both parameters obtained at the highest doses used. As fumonisins are unavoidable contaminants in food and feed chains, their presence needs to be reduced to minimize their effects on human and animal health and to diminish the annual market loss through rejected maize. In this scenario post-harvest use of chitosan could be an important alternative treatment.